Lower Triassic ammonites from Jameson Land (East Greenland) - Trümpy, Rudolf (Meddelelser om Grønland, 1969)
Description of Lower Eotriassic (Induan) ammonites from northern Jameson Land, especially Wegener Halvø. With the exception of few Otoceras, all belong to the Ophiceratids (Glyptophiceras, Metophiceras, Ophiceras, Paravishnuites and "Vishnuites"); most can be referred to species described by SPATH from Hold with Hope. A new subgenus to Glyptophiceras, Hypophiceras, is proposed for small forms from the very lowermost Triassic beds. Five new species are described and the zonal subdivision of the Eotriassic strata of East Greenland is discussed.